What Is the Current State of Training to Recognise and Treat Eating Disorders in Medical Schools in South Wales? - Thomas Prew; Rhiannon Kihara; Umer Jalal; Lois Bown; Isabella Jurewicz (BJPsych Open)
Aims: Eating disorders represent a major challenge for psychiatric and broader medical care. The rate of hospitalisation has almost doubled in recent years and anorexia has a higher mortality rate than any other mental illness. Beat Eating Disorders has made recommendations for educating medical students. When making the recommendations, they did not receive responses from Cardiff or Swansea Medical Schools. This review assesses the provision of eating disorder teaching and whether it is sufficient for effective medical training.